A Near-Field Clutter Artifact Mimicking Pulmonary Thrombus During Transesophageal Echocardiography. (October 2016) - Liang, Yafen; Alvis, Bret; Rice, Mark J.; Shaw, Andrew D.; Deitte, Lori A.; Eagle, Susan
Abstract : Supplemental Digital Content is available in the text.